2013
DOI: 10.2527/jas.2012-5168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lauric acid on ruminal protozoal numbers and fermentation pattern and milk production in lactating dairy cows1

Abstract: The objectives of this study were to evaluate lauric acid (LA) as a practical ruminal protozoa-suppressing agent and assess effects of protozoal suppression on fermentation patterns and milk production in dairy cows. In a pilot study, 6 lactating Holstein cows fitted with ruminal cannulae were used in a randomized complete-block design trial. Cows were fed a basal total mixed ration (TMR) containing (DM basis) 15% alfalfa silage, 40% corn silage, 30% rolled high moisture shelled corn, and 14% solvent soybean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 47 publications
2
17
2
2
Order By: Relevance
“…The latter could have caused toxic effect on ciliate protozoa due to its high levels of unsaturated fatty acids, considerable levels of lauric (C 12:0 ) and myristic (C 14:0 ) acids (Table 1). Both in vitro and in vivo studies have demonstrated protozoa sensitive to linolenic (C 18:3 ), linoleic (C 18:2 ), and oleic (C 18:1 ) unsaturated fatty acids, in this order (Machmüller et al, 1998;Hristov et al, 2004), and to lauric and myristic saturated fatty acids (Dohme et al, 1999;Faciola et al, 2013), with greater antiprotozoal effects observed with medium chain saturated lipids (Machmüller et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter could have caused toxic effect on ciliate protozoa due to its high levels of unsaturated fatty acids, considerable levels of lauric (C 12:0 ) and myristic (C 14:0 ) acids (Table 1). Both in vitro and in vivo studies have demonstrated protozoa sensitive to linolenic (C 18:3 ), linoleic (C 18:2 ), and oleic (C 18:1 ) unsaturated fatty acids, in this order (Machmüller et al, 1998;Hristov et al, 2004), and to lauric and myristic saturated fatty acids (Dohme et al, 1999;Faciola et al, 2013), with greater antiprotozoal effects observed with medium chain saturated lipids (Machmüller et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Other mechanisms for lipid toxicity that have been proposed were: perturbation of ether-lipid metabolism; inhibition of a specific-acyl-CoAacyltransferase, an enzyme involved in lipid-remodelling (Lux et al, 2000); and inhibition of methylation of phosphatidylcholine, which would block neo synthesis (Lira et al, 2001). Even though these studies were in flagellated protozoa, which have different membrane structure than rumen ciliates, these mechanisms may shed light into possible lipid toxicity mechanisms in rumen ciliates (Faciola et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…1). Nesse sentido, pesquisas realizadas in vitro e in vivo demonstraram que os protozoários são sensíveis aos ácidos graxos insaturados oleico (C18:1 cis-9), linoleico (C18:2 cis-9 cis-12) e α-linolênico (C18:3 n-3) (Machmüller et al, 1998;Hristov et al, 2004) e aos ácidos graxos saturados láurico e mirístico (Dohme et al, 1999;Faciola et al, 2013), sendo os dois últimos os que apresentam maior efeito tóxico sobre os protozoários ciliados do rúmen (Machmüller et al, 1998 A predominância do gênero Entodinium está de acordo com as observações dos autores que investigaram as populações de protozoários no rúmen de bovinos alimentados com dietas contendo óleo de soja, associado ou não à monensina (Martinele et al, 2008), de ovinos criados na caatinga (Matos et al, 2008), de bovinos e bubalinos alimentados com dietas suplementadas com monensina ou própolis (Risponli et al, 2009) e em caprinos submetidos à dieta com casca de soja, em substituição ao milho (Carvalho et al, 2011). Essa predominância pode ser justificada por esse gênero apresentar várias espécies de ampla distribuição e ocorrência entre vários ruminantes domésticos e selvagens (Ogimoto e Imai, 1981 A atividade antiprotozoária da TM na dieta poderia ter efeito positivo na eficiência de utilização da energia da dieta, uma vez que os protozoários podem ser responsáveis por até 37% de metanogênese (Finlay et al, 1994), e, portanto, uma redução dos ciliados pode resultar em menor perda de energia a partir do rúmen.…”
Section: Resultsunclassified
“…Essa predominância pode ser justificada por esse gênero apresentar várias espécies de ampla distribuição e ocorrência entre vários ruminantes domésticos e selvagens (Ogimoto e Imai, 1981 A atividade antiprotozoária da TM na dieta poderia ter efeito positivo na eficiência de utilização da energia da dieta, uma vez que os protozoários podem ser responsáveis por até 37% de metanogênese (Finlay et al, 1994), e, portanto, uma redução dos ciliados pode resultar em menor perda de energia a partir do rúmen. Além disso, pesquisadores têm relatado que a supressão de protozoários está intimamente relacionada com a redução da concentração de amônia no rúmen e o aumento da eficácia da síntese de proteína microbiana (Faciola et al, 2013;Fiorentini et al, 2013).…”
Section: Resultsunclassified
“…For example, there is evidence that antimicrobial synergy occurs in combinations of short-and long-chain fatty acids (Wang 1983). Fatty acids are toxic to both blood-borne (Doering et al 1994) and intestinal protozoa (Faciola et al 2012). Therefore, it is possible that fatty acids could be used to target cellulose-digesting protozoa in the guts of termites, resulting in individual and colony starvation.…”
Section: Discussionmentioning
confidence: 99%